Pengaruh Budaya Organisasi dan Kompetensi Terhadap Kinerja Karyawan PT. Semen Tonasa di Kabupaten Pangkep - Yasin, Hengky (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2024)
The problem in this study is whether cultural, organizational and competence have positive influence and signikfikan and which variables that have a dominant influence on employee performance PT. Semen Tonasa in Pangkep. To answer these problems we used descriptive analysis, quantitative analysis and multiple regression analysis. From the analysis of statistical tests showed that culture Organization and Competence positive and significant impact on employee performance PT. Semen Tonasa in Pangkep. From the results of the regression test showed that the variables that affect positively and significantly on employee performance and competency, namely Cultural Organization. Meanwhile, another case with variable dominant influence on employee performance is Cultural Organization, this is because the organizational culture has a regression coefficient values and t-count greater than the variable competence.